Technical success, clinical efficacy, and insight into the causes of restenosis after the percutaneous coronary intervention of de novo coronary artery lesions using a paclitaxel-coated balloon with citrate ester excipient - Tervo, Jerry; Kärkkäinen, Jussi M.; Rissanen, Tuomas T. (Frontiers in Cardiovascular Medicine, 2022)
Objectives The aim of this all-comers registry study was to investigate the technical success, clinical efficacy and safety of a drug-coated balloon (DCB) with paclitaxel combined with citrate ester excipient (CEE) in percutaneous coronary intervention (PCI) of de novo coronary lesions in an all-comers population. Methods A total of 338 consecutive PCIs using the DCB (CEE)-only approach comprising 406 de novo lesions were included in the study. Technical success was determined by the successful delivery of the device and no need for bailout-stenting. Results The mean follow-up time was 25±12 months. The mean age of patients was 71±11 years and 48% had an acute coronary syndrome. 55% of the patients at risk factor bleeding. The delivery of DCB was successful in 98% of cases. The overall technical success rate was 83%. Bailout stenting was used in 9% of lesions. Rotational atherectomy was used in 11% of cases before the DCB-only approach. The mean diameter of the DCBs used was 2.7±0.5 mm and 38% of DCBs were large (≥3.0mm). The 12-month MACE rates were 5.4±1.7% and 18.3±3.1% in stable CAD and in ACS, respectively. The respective TLR rates were 3.0±1.3% and 8.5±2.3%. Unacceptable acute recoil (>30%) was found in 74% cases that needed repeat revascularization. No acute vessel closures occurred after DCB treatment. Conclusions The DCB-only strategy using paclitaxel-coated (CEE) device was technically feasible, safe and effective in an all-comers population. Acute recoil was found as a significant cause of restenosis after DCB-only strategy.